2018
DOI: 10.1002/jso.25246
|View full text |Cite
|
Sign up to set email alerts
|

Early recurrence of well‐differentiated (G1) neuroendocrine liver metastasis after curative‐intent surgery: Risk factors and outcome

Abstract: Background The objective of the current study was to identify the risk of early vs late recurrence of well‐differentiated (G1) neuroendocrine liver metastasis (NELM) after curative‐intent resection. Methods Patients who underwent curative‐intent resection for well‐differentiated NELM were identified from a multi‐institutional database. Clinicopathological details, as well as the long‐term overall (OS) and recurrence free survival (RFS) were obtained and compared. The optimal cutoff value to differentiate early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, the prognostic impact of the combination of these features into a risk score for DR has been poorly investigated, with data derived from heterogeneous series, with relatively short follow-up after resection, and most studies focused exclusively on pancreatic NETs (PanNETs). [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The absence of a risk score for DR results in two major issues in post-surgical management. First, the efficacy of adjuvant treatments in radically resected EP-NETs still represents an unexplored option.…”
mentioning
confidence: 99%
“…However, the prognostic impact of the combination of these features into a risk score for DR has been poorly investigated, with data derived from heterogeneous series, with relatively short follow-up after resection, and most studies focused exclusively on pancreatic NETs (PanNETs). [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The absence of a risk score for DR results in two major issues in post-surgical management. First, the efficacy of adjuvant treatments in radically resected EP-NETs still represents an unexplored option.…”
mentioning
confidence: 99%
“…It has been well-documented that early recurrence after surgery leads to dismal prognosis (10)(11)(12). Because there is no consensus on the optimal threshold for differentiating early and late recurrence of GI-PDNEN, early recurrence was defined as recurrence within the 1st year after surgery, which is in line with that used in previous studies (10)(11)(12). With a relatively large sample size from one single-center institution in China, we demonstrated that the rate of early recurrence after curative surgery in GI-PDNEN was 30.7% and the median overall survival was 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-documented that early recurrence after surgery leads to dismal prognosis ( 10 12 ). Because there is no consensus on the optimal threshold for differentiating early and late recurrence of GI-PDNEN, early recurrence was defined as recurrence within the 1st year after surgery, which is in line with that used in previous studies ( 10 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…While long-term OS generally is excellent, recurrence following hepatic resection of NELM can approach 50-95%, and the majority of recurrences will occur in the liver (21,40). Among patients who develop intrahepatic recurrence, >70% will occur within 3 years of surgery, and approximately 40% within 1 year (34,43). Multiple studies have highlighted the safety and relative efficacy of repeat hepatectomy for recurrent primary and metastatic liver disease (44,45); repeat hepatic resection for recurrent NELM has similarly been demonstrated to be feasible and associated with good long-term survival outcomes in wellselected patients (46).…”
Section: Recurrent Diseasementioning
confidence: 99%